2013
DOI: 10.3892/etm.2013.1155
|View full text |Cite
|
Sign up to set email alerts
|

Combination treatment with asiaticoside and rapamycin: A new hope for in-stent restenosis

Abstract: The aim of this study was to investigate and characterize the efficacy and mechanism of action of asiaticoside in combination with rapamycin in the inhibition of in-stent restenosis (ISR). The effects of asiaticoside combined with rapamycin on cell proliferation in vitro were evaluated by MTT assay. The mRNA expression was analyzed by quantitative polymerase chain reaction (qPCR). Enzyme-linked immunosorbent assay (ELISA) was used to confirm protein synthesis. The cell growth inhibition rate in the combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The RT-qPCR results suggest that the mRNA expression levels of MMP-9 were increased and those of TGF-β1 were reduced in group A compared with those in group B. Since MMP-9 and TGF-β1 are crucial factors associated with pulmonary fibrosis (3,26), these results demonstrate that BMSCs, particularly when transfected with survivin, may be able to reduce bleomycin-induced pulmonary fibrosis in mice, which is consistent a previous report (21). Furthermore, previous studies have indicated that BMSCs secrete a variety of cell factors that participate in vascular regeneration and endothelial cell remodeling in lung tissue, and these factors may induce BMSCs to differentiate (6,27).…”
mentioning
confidence: 99%
“…The RT-qPCR results suggest that the mRNA expression levels of MMP-9 were increased and those of TGF-β1 were reduced in group A compared with those in group B. Since MMP-9 and TGF-β1 are crucial factors associated with pulmonary fibrosis (3,26), these results demonstrate that BMSCs, particularly when transfected with survivin, may be able to reduce bleomycin-induced pulmonary fibrosis in mice, which is consistent a previous report (21). Furthermore, previous studies have indicated that BMSCs secrete a variety of cell factors that participate in vascular regeneration and endothelial cell remodeling in lung tissue, and these factors may induce BMSCs to differentiate (6,27).…”
mentioning
confidence: 99%